EFEKTIVITAS PERDA KOTA BANDUNG NO. 9 TAHUN 2019 DALAM MENGATASI AKTIVITAS PENGAMEN DAN PENGEMIS: PERSPEKTIF PELAKU DAN MASYARAKAT - Pramesty, Adhisty Tinka; Mahpudz, Asep; Fitria, Ratna (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2025)
The high prevalence of street performers and beggars in public spaces of Bandung City continues despite the enactment of Bandung City Regional Regulation No. 9 of 2019. Preventive to repressive measures have been taken, yet the outcomes remain suboptimal. This study aims to understand the responses of those affected by the policy by examining the level of legal awareness and compliance among street performers, beggars, and the general public; identifying factors contributing to low compliance; and formulating improvement strategies for regulation implementation. This research employs a qualitative method with a case study approach, using interviews, observations, and documentation involving street performers, beggars, and the public in Bandung City. The findings reveal that legal awareness and compliance among both the perpetrators and the community are relatively low. Most informants cited poverty as the primary reason for engaging in street performing or begging, while the influence of a socially acculturated environment and the lack of economic alternatives within the policy also contribute to low compliance. From the community’s perspective, social compassion, passive attitudes, and a tendency to remain neutral without supporting law enforcement further drive the low level of legal awareness and compliance. This study recommends the provision of sustainable economic empowerment programs as alternative livelihoods for the affected individuals, enhanced legal education and outreach efforts, and a more human-centered approach to regulation implementation that emphasizes human empowerment to foster meaningful long-term change.